Tindak Pidana Contempt of Court Perspektif Hukum Islam - Musyafaah, Nur Lailatul; Warjiyati, Sri; Syafaq, Hammis (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
The court is a place to seek justice. It is a place that must be respected. However, there are still many cases of contempt of court.  This is contrary to the Criminal Code and Islamic law.  This study examines the contempt of court perspective of Islamic law. This research is a library and qualitative research. Data collection is carried out through literature studies derived from laws, books, and journals. The collected data is described for deductive analysis using Islamic law. The results of the study mentioned that in Indonesia there is no specific law on Contempt of court.  Contempt of court is based on criminal code articles 210, 2lindung16, 217, 221, 222, 223, 224, 225, 242, 222, 231, 232, 233, 317, 417, 552.  In Islamic law, contempt of court is a prohibited act as described in the Qur'an and hadith. The sentence is in accordance with the form of the contempt of the court perpetrator's actions and the consequences they cause. If the terms of his sentence are not mentioned in the Qur'an and hadith, then the judge can decide based on his ijtihad called ta'zir.